Download presentation
Presentation is loading. Please wait.
Published byDarrell Matthews Modified over 9 years ago
1
3.3 – Slope
2
Recall how to graph y = 2x – 3. 3.3 – Slope
3
Recall how to graph y = 2x – 3. 3.3 – Slope
4
Recall how to graph y = 2x – 3. x 3.3 – Slope
5
Recall how to graph y = 2x – 3. x 0 1 3.3 – Slope
6
Recall how to graph y = 2x – 3. x2x – 3 0 1 3.3 – Slope
7
Recall how to graph y = 2x – 3. x2x – 3y 0 1 3.3 – Slope
8
Recall how to graph y = 2x – 3. x2x – 3y(x, y) 0 1 3.3 – Slope
9
Recall how to graph y = 2x – 3. x2x – 3y(x, y) 2(-1) – 3-5(-1, -5) 02(0) – 3-3(0, -3) 12(1) – 3(1, -1) 3.3 – Slope
10
Recall how to graph y = 2x – 3. x2x – 3y(x, y) 2(-1) – 3-5(-1, -5) 02(0) – 3-3(0, -3) 12(1) – 3(1, -1) 3.3 – Slope
11
Recall how to graph y = 2x – 3. x2x – 3y(x, y) 2(-1) – 3-5(-1, -5) 02(0) – 3-3(0, -3) 12(1) – 3(1, -1) 3.3 – Slope
12
Recall how to graph y = 2x – 3. x2x – 3y(x, y) 2(-1) – 3-5(-1, -5) 02(0) – 3-3(0, -3) 12(1) – 3(1, -1) 3.3 – Slope
13
Slope
14
Slope = Change in y Change in x
15
Slope = Change in y Change in x m = y 2 – y 1 x 2 – x 1
16
Slope = Change in y Change in x m = y 2 – y 1, x 2 – x 1 for (x 1,y 1 ) and (x 2,y 2 )
17
Slope = Change in y Change in x m = y 2 – y 1, x 2 – x 1 for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
18
Slope = Change in y Change in x m = y 2 – y 1, Slope = x 2 – x 1 for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
19
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
20
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
21
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
22
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
23
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
24
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
25
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256*
26
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4)
27
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4)
28
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) m = y 2 – y 1 x 2 – x 1
29
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 m = y 2 – y 1 x 2 – x 1
30
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 m = y 2 – y 1 x 2 – x 1
31
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 m = y 2 – y 1 x 2 – x 1
32
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1
33
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) (3 – (-1))
34
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2
35
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2
36
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2
37
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2
38
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2
39
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2 1
40
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2 1
41
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2 2 1
42
Slope = Change in y Change in x m = y 2 – y 1, Slope = rise x 2 – x 1 run for (x 1,y 1 ) and (x 2,y 2 ) *See bottom p.256* Ex. 1 Find the slope of the lines through the following points: a. (-1,2) and (3,4) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1 = (4 – 2) = 1 (3 – (-1)) 2 2 1
43
b.
44
b. Slope =
46
b. Slope = -1
48
3
49
b. Slope = -1 3 c. (1,2) and (-1,2)
50
b. Slope = -1 3 c. (1,2) and (-1,2) x 1 y 1 x 2 y 2
51
b. Slope = -1 3 c. (1,2) and (-1,2) x 1 y 1 x 2 y 2 m = y 2 – y 1 x 2 – x 1
52
b. Slope = -1 3 c. (1,2) and (-1,2) x 1 y 1 x 2 y 2 m = y 2 – y 1 = (2 – 2) x 2 – x 1 -1 – 1
53
b. Slope = -1 3 c. (1,2) and (-1,2) x 1 y 1 x 2 y 2 m = y 2 – y 1 = (2 – 2) = 0 x 2 – x 1 -1 – 1 -2
54
b. Slope = -1 3 c. (1,2) and (-1,2) x 1 y 1 x 2 y 2 m = y 2 – y 1 = (2 – 2) = 0 = 0 x 2 – x 1 -1 – 1 -2
55
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year.
58
***Time is always the independent (x) variable!
59
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year. ***Time is always the independent (x) variable! m = y 2 – y 1 x 2 – x 1
60
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year. ***Time is always the independent (x) variable! m = y 2 – y 1 x 2 – x 1
61
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year. ***Time is always the independent (x) variable! m = y 2 – y 1 = (62,424 – 55,280) x 2 – x 1 (1998 – 1990)
62
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year. ***Time is always the independent (x) variable! m = y 2 – y 1 = (62,424 – 55,280) x 2 – x 1 (1998 – 1990) = 7144 8
63
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year. ***Time is always the independent (x) variable! m = y 2 – y 1 = (62,424 – 55,280) x 2 – x 1 (1998 – 1990) = 7144 8 = 893
64
Ex. 2 In 1990, the average annual household income was $55,280. It then rose to $62,424 in 1998. Based on this information, at what rate did the average annual household income change per year. ***Time is always the independent (x) variable! m = y 2 – y 1 = (62,424 – 55,280) x 2 – x 1 (1998 – 1990) = 7144 8 = 893 = $893/yr.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.